Symbolic Violence Through Negative Stereotypes Against Private School Students in Bantaeng Regency - Suardi, Suardi (Jurnal Mamangan, 2023)
The research problem is the existence of symbolic violence against private school students through stereotypes. The purpose of the study was to analyze negative stereotypes against private school students as a means of symbolic violence. This research was conducted using the mixed method concurrent embedded method in 10 private schools and 6 public schools. Qualitative research informants as many as 43 people were determined using purposive sampling while 301 quantitative research respondents were determined using random sampling. Data was collected using a Likert and Gutman scale questionnaire, direct observation sheets, structured interview sheets and documents. The qualitative data that has been collected is analyzed through the stages of data reduction, displaying the data and then drawing conclusions, while the quantitative data is analyzed through the stages of verification, tabulation and data percentage. The results show that symbolic violence occurs because of negative stereotypes against private school students and stereotypes against actors or private schools carried out by public school actors who have accumulated capital, power in the world of education.